First-principles investigation of structural, electronic, optical, and thermoelectric properties of Li2X (X = Te, Se, S) chalcogenides for energy and optoelectronic applications - Muhammad Uzair; Rajwali Khan; Ayesha Nawab; Asim Sajjad; Sohail Mumtaz; Nourreddine Sfina; Vineet Tirth; Ali Algahtani; M.D. Alshahrani; Salma Alshehri; Mudasser Husain; Nasir Rahman (Results in Physics)
The structural, electronic, optical, elastic, and thermoelectric properties of Li2X (X = S, Se, Te) chalcogenides were systematically investigated using density functional theory. Volume-energy analysis via Birch-Murnaghan fitting reveals that Li2S exhibits the greatest structural stability. The bandgaps decrease from Li2S (∼3.2 eV) to Li2Se (∼1.8 eV) and Li2Te (∼1.0 eV), correlating with lattice constants and chalcogen mass. Li2Te’s narrow direct bandgap and strong hybridization suggest thermoelectric potential, while Li2Se is promising for optoelectronics. Li2S, with a wide bandgap and high ionic conductivity, is ideal for optical and solid-state electrolyte applications. Elastic analysis shows Li2Se is the stiffest and most ductile, while Li2Te and Li2S show greater anisotropy. Optical results confirm that heavier chalcogens enhance reflectivity and metallicity, whereas lighter ones promote insulating behavior. These findings demonstrate the tunability of Li2X compounds for diverse energy and electronic applications.